Pharmacoeconomic analysis of dexamethasone intravitreal implant for the treatment of diabetic macular edema in Russia - A. S. Kolbin; T. L. Galankin; A. I. Kaleev (Izdatelstvo OKI, 2018)
A health economic study was conducted under the Russian economic conditions to evaluate the feasibility of the use of dexamethasone 0.7 mg as a sustained release intravitreal implant (hereinafter, DEX implant) in the treatment of diabetic macular edema. Cost-effectiveness analyses (CEA) were performed using a decision tree model with calculation of cost effectiveness ratios (CER), as well as incremental cost-effectiveness and cost-utility ratios (ICER and ICUR). Ranibizumab 10 mg/ml, solution for intravitreal administration (hereinafter, ranibizumab), and aibercept 40 mg/ml, solution for intravitreal administration (hereinafter, aibercept), were used as the comparator drugs; the modeling study covered a three-year period. A probabilistic sensitivity analysis (PSA) was carried out to evaluate the level of uncertainty of the obtained results. A budget impact analysis was also performed. Free scenarios were reviewed for each analysis: the main scenario for phakic and pseudophakic eyes with the weighted average effects of the study drugs; alternative scenario 1 for pseudophakic eyes with the weighted average effects; alternative scenario 2 for pseudophakic eyes with the maximum possible effects of the study drugs. A network meta-analysis of 10 randomized controlled studies (RCT) was performed to evaluate the weighted average effect. e maximum possible effects were determined based on specific studies, including observational studies. e results of the main scenario and alternative scenario 1 demonstrated that the comparator drugs were inferior to the DEX implant with regard to the economic feasibility, since they had higher CER; the ICER and ICUR for the comparator drugs exceeded the social willingness to pay threshold. e results of alternative scenario 2 demonstrated that the DEX implant was dominant with regard to ranibizumab, and it was superior to aibercept with regard to the CER, ICER, and ICUR. The budget impact analysis demonstrated that a 3-year use of the DEX implant will allow to save the funds equivalent to an additional treatment of 102-189 patients if it replaces ranibizumab (depending on the scenario) or 72-286 patients if it replaces aibercept (depending on the scenario). e sensitivity analysis demonstrated low level of uncertainty of study conclusions.